A Systematic Literature Review: Restorative Justice Approaches Resolving Violations of Electronic Information and Transaction Laws in Indonesia - Edgar Irvin Raranta (Jurnal Syntax Admiration, 2024)
The evolution of society into the information era, propelled by globalization and technological advancements, has transformed social behaviors and interactions, giving rise to the concept of an "information society." However, the proliferation of communication technology, while beneficial, has also presented challenges in ensuring responsible usage. This study explores the application of Restorative Justice Approaches in addressing violations of electronic information and transaction laws in Indonesia. Through a Systematic Literature Review method, five relevant studies were analyzed, revealing the efficacy and versatility of Restorative Justice in resolving various cybercrimes, including defamation, hate speech, dissemination of false information, and pornography. Despite its benefits, challenges such as disagreements among involved parties, resource limitations, and regulatory gaps hinder the effective implementation of Restorative Justice. Addressing these obstacles is crucial for fostering fair reconciliation and optimizing outcomes in resolving electronic information and transaction law violations